The Ascidiacea collected during the 2017 British Columbia Hakai MarineGEO BioBlitz - Lambert, Gretchen (Zootaxa, 2019)
A three-week intensive marine biodiversity survey was carried out at a small remote region of the central British Columbia coast at and near the Calvert Island Marine Station (Hakai Institute) July 21–August 11, 2017. The survey included daily sampling by the staff and a number of visiting taxonomists with specialties covering all the major groups of invertebrates. Many marine habitats were sampled: rocky and sand/gravel intertidal and tidepools, eelgrass meadows, shallow and deeper subtidal by snorkel and Scuba, plus artificial surfaces including the sides and bottom of the large floating dock at the Institute and settlement plates set out up to a year previously at various subtidal sites. Many new species were recorded by all the taxonomists. In this very biodiverse remote area 36 ascidian species were identified: 18 Aplousobranchia, 7 Phlebobranchia, and 11 Stolidobranchia, comprising a total of 15 solitary and 21 colonial species including two undescribed colonial species. This represents almost one third of all the known North American species from Alaska to southern California in this limited very remote area. Remarkably, only two are possible non-natives. Diplosoma listerianum (Milne-Edwards, 1841), was collected mostly on natural substrates including deeper areas sampled by Scuba, and one colony occurred on a settlement plate. A few Ciona savignyi Herdman, 1882 were collected, two from natural substrates and four from artificial surfaces. There were no botryllids, Styela clava Herdman, 1881, Didemnum vexillum Kott, 2002, or Molgula manhattensis (De Kay, 1843), though these are all common and sometimes very abundant non-natives in other parts of BC and along much of the U.S. west coast. Most of the species encountered are known in northern California, Washington, and southern BC, but only a small number are represented among the few known Alaska species.